Money and inflation in Switzerland - Peter Kugler; Samuel Reynard (Swiss Journal of Economics and Statistics, 2022)
This paper characterizes the relationship between monetary aggregates, inflation and economic activity in Switzerland since the mid-1970s. Traditional forms of money demand and quantity theory relationships have remained stable over the whole period. Broad money excesses over trend values, accounting for a secular decline in interest rates and thus in trend velocity, have been followed by persistently higher inflation and output with the usual monetary policy transmission lags. Money and exchange rate fluctuations can explain the major inflation developments in Switzerland over the past four decades.
Keywords: E52; E58; E41; E30; 330; Monetary policy; Monetary aggregates; Inflation; Trend velocity